Back to Basics: Environmental Cleaning Hazards. (27th October 2017) - Spruce, Lisa
Abstract: Perioperative personnel must clean and disinfect the perioperative environment numerous times throughout the day to help prevent the risk of exposing patients to pathogenic microorganisms. However, this practice exposes perioperative team members to chemicals that could be harmful to their health. Exposure to cleaning and disinfecting products has been associated with potential health problems such as skin irritation, burns, rashes, and difficulty breathing. This Back to Basics article offers strategies for perioperative team members to implement to decrease their risk of harmful exposure to these products.